Road-testing the first turnpikes. The enduring value of Daniel Defoe's account of English highways. Issue 2 (August 2019) - Rogers, Pat
A famous appendix, devoted mainly to the state of English roads, appeared in the second volume of Daniel Defoe's Tour thro' the Whole Island of Great Britain (1724–26). Though cited on countless occasions by historians over almost three centuries, the text has never been properly edited with detailed attention to its coverage of the newly emergent method of maintaining roads through the establishment of turnpike trusts. In default, this study seeks to describe major features of the account, to indicate its timeliness, and to set out the factors which enabled Defoe to provide an unrivalled picture of the communications network of his time. The appendix carries even more weight because it fills out a comprehensive survey of road conditions throughout the text, as part of the author's overall design in the Tour. This shows the interdependence of separate regions of the country, bound together in a system centred on London.